2012
DOI: 10.1158/1078-0432.ccr-12-0782
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Efficacy of New Hsp90 Inhibitors Revealed by Ex Vivo Culture of Human Prostate Tumors

Abstract: Purpose: Targeting Hsp90 has significant potential as a treatment for prostate cancer, but prototypical agents such as 17-allylamino-17 demethoxygeldanamycin (17-AAG) have been ineffective in clinical trials. Recently, a phase I study aimed at defining a biologically active dose reported the first response to an Hsp90 inhibitor in a patient with prostate cancer, which supports the development of new generation compounds for this disease.Experimental Design: The biological actions of two new synthetic Hsp90 inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 27 publications
8
128
0
Order By: Relevance
“…Fresh prostate cancer tissues were obtained with informed consent from men undergoing radical prostatectomy at the Hospitals of the University of Texas Southwestern Medical Center (Dallas, TX) 43 (see Supplementary Table S2 for clinicopathological characteristics). The tissues were dissected into 1 mm 3 pieces and randomly placed in triplicates on a pre-soaked 1-cm 3 veterinary dental sponge (Novartis, East Hanover, NJ) inside the wells of a 12-well plate containing 600 ml RPMI 1640 with 5% heat-inactivated FBS, 100 units per ml penicillin-streptomycin and vehicle (DMSO) alone, D1 (100 nM) or D2 (100 nM).…”
Section: Methodsmentioning
confidence: 99%
“…Fresh prostate cancer tissues were obtained with informed consent from men undergoing radical prostatectomy at the Hospitals of the University of Texas Southwestern Medical Center (Dallas, TX) 43 (see Supplementary Table S2 for clinicopathological characteristics). The tissues were dissected into 1 mm 3 pieces and randomly placed in triplicates on a pre-soaked 1-cm 3 veterinary dental sponge (Novartis, East Hanover, NJ) inside the wells of a 12-well plate containing 600 ml RPMI 1640 with 5% heat-inactivated FBS, 100 units per ml penicillin-streptomycin and vehicle (DMSO) alone, D1 (100 nM) or D2 (100 nM).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were treated as indicated for 4 days and counted as previously described (Centenera et al 2012). The caspase inhibitor z-VAD-fmk (50 mM) was included for the duration of the relevant experiments.…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 99%
“…Unfortunately, 17-AAG did not show its predicted clinical efficacy as a single agent in CRPC, due to toxicity and poor pharmacodynamic properties that prevented therapeutic doses being achieved (Banerji et al 2005, Heath et al 2008, Ramanathan et al 2010. While more potent inhibitors such as AUY922 are currently being developed and show promise as single agents (Samuel et al 2010, Centenera et al 2012, recent evidence of additive or synergistic activity between 17-AAG and cytotoxic agents or specific molecular therapeutics provides a promising new avenue of clinical development for this drug . In preclinical prostate cancer studies, 17-AAG or AUY922 combined with ionizing radiation has demonstrated supra-additive reductions in tumor growth and clonogenicity (Enmon et al 2003, Ochel & Gademann 2006, Gandhi et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…It is also applicable to multiple solid tumor types; to date, the methodology has successfully been applied to all cancers tested, including some not represented in the current study (ovary, endometrium, renal, sarcoma; personal communication). The de novo cellular proliferation observed in cultured tissues indicates that the system is not static and makes this a particularly useful model to assess the growth inhibitory activity of new or emerging therapeutic agents, as demonstrated by our respective teams using PDEs from prostate cancer and breast cancer (Centenera et al ., 2012; Comstock et al ., 2013; Dean et al ., 2012; de Leeuw et al ., 2015; Schiewer et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Despite observing significant effects of bicalutamide on PDE proliferative index, apoptotic response to bicalutamide was also evaluated, using the immunohistochemistry marker cleaved caspase‐3. We have previously reported apoptosis induction in prostate cancer PDEs cultured for 48 h with other therapeutic agents (Centenera et al ., 2012). It is therefore likely that higher doses of bicalutamide than the 10 μ m used in this study are required to induce apoptosis in prostate cancer PDEs.…”
Section: Discussionmentioning
confidence: 99%